Present and potential distribution of two Mimosa (Leguminosae) taxa endemic to Mexico - Montaño-Arias, Susana Adriana (2018)
Mimosa aculeaticarpa var. aculeaticarpa and M. luisana are endemic to Mexico, and are considered as multipurpose plants, due to the diverse services they offer to ecosystems and to local people. Additionally, they are appreciated for their potential to restore tropical environments; hence, the objective of this study was to model the present and potential distribution of these taxa. In 2014, species registers were obtained from two databases (CONABIO and MEXU); each register was taxonomically, geographically and statistically validated. Once validated, the present and potential distribution of M. aculeaticarpa var. aculeaticarpa (based on 99 registers) and M. luisana (based on 50 registers) were obtained using the MAXENT algorithm. For both taxa, the present distribution was overlapped using the layers of: elevation, climate, soil, biogeographic provinces, and hydrologic basins. Mimosa aculeaticarpa var. aculeaticarpa showed a wide distribution in Mexico (16 states); whilst M. luisana was restricted to the states of Puebla and Oaxaca. M. aculeaticarpa var. aculeaticarpa establishes between 1 900 and 2 700 masl, and M. luisana between 500 and 1 760 masl. Both species were established in arid and semiarid climates; however, M. aculeaticarpa var. aculeaticarpa can also be found in temperate and mesic climates. Moreover, both taxa are distributed in calcareous regosol soils; although, M. aculeaticarpa var. aculeaticarpa is also found in eutric regosol, chromic vertisol and haplic phaeozem. The distribution of M. aculeaticarpa var. aculeaticarpa includes eight biogeographic provinces and three hydrologic basins; whilst M. luisana was only located in three provinces and two hydrologic basins; both are present in the Eje Volcánico and Sierra Madre del Sur provinces. The potential distribution models are considered as excellent ones due to an AUC of 0.91 and 0.97, respectively; these models indicated that the temperature and precipitation conditions would be suitable for the enlargement of their distribution. Likewise, these models can be considered an approach to the potential distribution knowlegment of the Mexican mimosas. Nevertheless, it is important to note that the models are static and do not take into account any biotic interaction; therefore, their relationship with reality can vary. Thus, it is recommended to analyze the models through different climate change and land use scenarios.